A 20 km/80 Gbps bidirectional PON employing three-stage injection-locked VCSELs/NDFs/OBPFs. (10th November 2015) - Ying, Cheng-Ling; Lu, Hai-Han; Li, Chung-Yi; Lin, Che-Yu; Wan, Zhi-Wei; Cheng, Chun-Jen
Abstract: A 20 km/80 Gbps bidirectional passive optical network (PON) employing three-stage, injection-locked, 1.55 μ m, vertical-cavity surface-emitting lasers (VCSELs), negative dispersion fibers (NDFs), and optical band-pass filters (OBPFs) is proposed and demonstrated. The three-stage injection-locked technique, which can greatly increase the frequency response of VCSELs, is thereby expected to provide excellent transmission performance in a bi-directional PON. To be the first one of employing directly modulated, three-stage injection-locked, 1.55 μ m, VCSELs; NDFs; and OBPFs results in excellent bit error rate (BER) performance, and clear eye diagrams are obtained for 20 km/80 Gbps, bidirectional PON applications. Such a novel bidirectional PON provides the advantage of a communication link for high data rates that could accelerate bidirectional PON deployment.